Re-description of the assassin bug species Pygolampis striata Miller, 1940 with new distributional records from Japan and Indonesia (Heteroptera, Reduviidae, Stenopodainae) - Kyosuke Okuda (Biodiversity Data Journal, 2021)
Pygolampis striata Miller, 1940 is described based on a single male specimen. However, there are no records of the species since then. Therefore, the females and nymphs have not been described, and knowledge about their habitat is insufficient.This is the first record of the Assassin bug Pygolampis striata Miller, 1940 from Japan and Indonesia. Here, this species has been re-described, and for the first time, the female has been described. The species was collected from the surfaces of dried Poaceae grasslands using the "Gasa-Gasa collecting method".